Mirror, Mirror by the Stairs: The Impact of Mirror Exposure on Stair versus Elevator Use in College Students - Katie L Hodgin; Dan J Graham (Frontiers Media S.A., 2016)
AbstractPrevious research has indicated that self-awareness-inducing mirrors can successfully incite behaviors that align with one's personal values, such as helping others. Other research has found a large discrepancy between the high percentage of young adults who report valuing the healthfulness of physical activity (PA) and the low percentage who actually meet PA participation standards. Few studies, however, have examined how mirror exposure and both perceived and actual body size influence highly-valued PA participation among college students. The present study assessed stair versus elevator use on a western college campus and hypothesized that mirror exposure would increase the more personally-healthy transportation method of stair use. In accordance with previous research, it was also hypothesized that males and those with a lower body mass index (BMI) would be more likely to take the stairs, and that body-size distorting mirrors would impact the stair-elevator decision. One hundred and sixty-seven students (51% male) enrolled in an introductory psychology course were recruited to take a survey about their transportation choices at an indoor campus parking garage. Participants were individually exposed to either no mirror, a standard full-length mirror, or a full-length mirror manipulated to make the reflected body size appear either slightly thinner or slightly wider than normal before being asked to go to the fourth floor of the garage for a survey. Participants' choice of floor climbing method (stairs or elevator) was recorded and they were administered an internet-based survey assessing demographic information, BMI, self-awareness, perceived body size, and other variables likely to be associated with stair use. Results from logistic regression analyses revealed that participants who were not exposed to a mirror (OR = 0.37, 95% CI: 0.14 - 0.96), males (OR = 0.33, 95% CI: 0.13 - 0.85), those with lower BMI (OR = 0.84, 95% CI: 0.71 - 0.99), those with higher exercise participation (OR = 1.09, 95% CI: 1.02 - 1.18), and those engaging in more unhealthy weight-control behaviors (OR = 1.55, 95% CI: 1.14 - 2.11) showed increased odds of taking the stairs. Implications and future directions are discussed.